A new species of genus Acheilognathus, Bleeker, 1895 from the Tien Yen river, Vietnam - Duc, Nguyen Huu; Hau, Tran Duc; Thuy, Ta Thi (Academia Journal of Biology, 2013)
Acheilognathus nguyenvanhaoi Nguyen H. D., Tran D. H. & Ta T. T. sp. n. Holotype: MB-HNUE VI.1-F01; female, 51.4 mm SL; Vietnam: Quang Ninh Prov., Tien Yen River at Binh Lieu town; Nguyen Huu Duc et al., 14 March 2011. Paratype: 1 MB-HNUE VI.1-F02, male, 60.5 mm SL. Same data as holotype. Diagnosis: When Acheilognathus nguyenvanhaoi sp. n. is compared with closely related species of Acheilognathus, it is characteristic in the five following traits: a broad and dark longitudinal stripe on body (both sides) running from tip of snout to tip of middle caudal fin rays, not tapering anteriorly vs. a narrower and lighter one running most anteriorly behind operculum to caudal base, tapering anteriorly; pharyngeal teeth (5.1-0.5, vs. 5-5); spiny rays of dorsal and anal fins (III-IV, vs. III) and scales above lateral line (7, vs less than 6). The new species differed from A. meridianus and A. barbatus in number of predorsal scales; from A. meridianus, A. barbatulus and A. melanogaster in number of vertebrae; from A. melanogaster in lenght of barbel; from A. brevicaudatus and A. melanogaster in number of gill rackers on the outer side of the first gill arch and from A. barbatulus and A. melanogaster in proportion between anterior and posterior length of gas-bladder. Description: SL = 3.09-3.13 BD = 4.48-4.62 HL = 1.97-2.02 PDL = 4.05-4.84 LCP = 7.76-8.48 CPD; HL = 2.76-3.05 OD = 2.70-2.76 IOW. Body compressed. Mouth sub-inferior. Barbels present. Dorsal fin with 3-4 non-segmented spiny soft rays and 9 branched rays. Anal fin with 3-4 non-segmented spiny soft rays and 10-11 branched rays. Pectoral fin with one segmented spiny soft ray and 11 branched rays. Pelvic fin with one segmented spiny soft ray and 7 branched rays. Lateral line complete with 36-37 pored scales. Predorsal scales 13-14; Scales around caudal peduncle 14-15; Gill rakers on external side of first gill arch 9; Pharyngeal teeth 5.1-0.5. Vertebrae 37-38. Inserted position of first proximal pterygiophores in the dorsal and anal fins as 10th-11th and 18th, respectively. Colour in preservative: Body yellowish. A board longitudinal dark stripe on body running from the tip of snout to the tip of the middle caudal fin rays, not tapering anteriorly. Distribution: Presently known only from the Tien Yen river, Quang Ninh province, Northern Vietnam at Binh Lieu town. Etymology: Named for Nguyen Van Hao, a Vietnamese ichthyologist.